Accumulative weekly external and internal load relative to match load in elite male youth soccer players - de Dios-Álvarez, V.; Alkain, P.; Castellano, J.; Rey, E. (Pediatric Exercise Science, 2022)
The aim of this study was 2-fold: (1) to assess and compare the external and internal load of elite young soccer players during competitive microcycles and (2) to describe the training/match ratios (TMr) in elite male youth soccer players.